Comparative study on the effect of bentonite or feldspar filled low-density polyethylene/thermoplastic sago starch/kenaf core fiber composites - Sarifuddin, Norshahida; Ismail , Hanafi (College of Natural Resources, North Carolina State University, 2013)
The present work evaluated the potential of the addition of bentonite and feldspar as fillers on the mechanical and physical properties of low-density polyethylene (LDPE)/thermoplastic sago starch (TPSS)/kenaf core fiber (KCF) composites. For this purpose, 3 to 15 phr of fillers were incorporated into LDPE/TPSS/KCF composites that were fabricated via a melt-mixing molding system. Results showed that the tensile strength and modulus were improved significantly with the addition of bentonite in comparison with feldspar. Thermal studies confirmed the improvement in thermal stability of composites filled with bentonite as well as feldspar. An increased percentage of water absorption was also observed in these composites compared with the control (LDPE/TPSS/KCF composites) system.